2020
DOI: 10.2215/cjn.08060719
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Position and Incidence of Glomerular Diseases

Abstract: Background and objectives Social deprivation is a recognized risk factor for undifferentiated CKD; however, its association with glomerular disease is less well understood. We sought to investigate the relationship between socioeconomic position and the population-level incidence of biopsy-proven glomerular diseases. Design, setting, participants, & measurements In this retrospective cohort study, a provincial kidney pathology database (2000-2012) was used to capture all incident cases of membranous nephropath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
13
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 44 publications
2
13
0
Order By: Relevance
“…Alternatively, because socioeconomic position is a surrogate for innumerable individual health behaviors and social and physical environmental factors, drivers of the association between socioeconomic position and glomerular disease risk might differ in Canada compared with in other regions. In particular, universal access to health care in Canada should minimize differences in missed or delayed diagnoses as supported by the broadly similar laboratory values at presentation across socioeconomic groups in the study by Canney et al (9). Accordingly, differences in disease incidence identified in this study are more likely to be explained by differences in health behaviors or social and environmental hazards than by inequitable access to preventative or diagnostic health care services.…”
supporting
confidence: 57%
See 2 more Smart Citations
“…Alternatively, because socioeconomic position is a surrogate for innumerable individual health behaviors and social and physical environmental factors, drivers of the association between socioeconomic position and glomerular disease risk might differ in Canada compared with in other regions. In particular, universal access to health care in Canada should minimize differences in missed or delayed diagnoses as supported by the broadly similar laboratory values at presentation across socioeconomic groups in the study by Canney et al (9). Accordingly, differences in disease incidence identified in this study are more likely to be explained by differences in health behaviors or social and environmental hazards than by inequitable access to preventative or diagnostic health care services.…”
supporting
confidence: 57%
“…The study by Canney et al (9) in this issue of CJASN represents an important step toward closing this knowledge gap. In their analysis, the investigators identified all biopsies performed in the province of British Columbia, Canada over a 13-year period (2000-2012) using an existing centralized kidney pathology database.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…[10][11][12][13] Considering socioeconomic factors, several studies have explored a possible link between socioeconomic deprivation and incidence of AAV with mixed results. [14][15][16] We recently demonstrated a twofold increased risk of death in patients with primary glomerulonephritis living in relative socioeconomic deprivation. 17 Chronic kidney disease (CKD) is more common in areas of social deprivation 18 and individuals living in these areas are more likely to progress to ESKD.…”
Section: Key Messagesmentioning
confidence: 99%
“…I was greatly interested in the findings of a recent study published in this issue of CJASN on socioeconomic status and kidney disease in British Columbia (1). I did in-center hemodialysis for 3 years and saw people from a variety of socioeconomic backgrounds there.…”
mentioning
confidence: 99%